Biological characterization and variability of the nucleocapsid protein gene of Groundnut bud necrosis virus isolates infecting pea from India - AKRAM, Mohammad; NAIMUDDIN (Phytopathologia Mediterranea, 2012)
A disease of pea characterized by browning in veins, leaves and stems, mostly in growing tips, and brown circular spots on pods, was recorded in four districts of Uttar Pradesh, India. The causal agent of this disease was detected by reverse transcription-polymerase chain reaction (RT-PCR) using primers pair HRP 26/HRP 28 and identified as Groundnut bud necrosis virus (GBNV) on the basis of nucleocapsid protein (NP) gene sequence. Virus isolates from Bareilly (BRY), Kanpur (KNP), Udham Singh Nagar (USN) and Shahjahanpur (SJP) were designated as GBNV-[Pea_BRY], GBNV-[Pea_KNP], GBNV-[Pea_USN] and GBNV-[Pea_SJP] and their NP genes sequenced. The sequence data of each isolate were deposited at NCBI database (JF281101-JF281104). The complete nucleotide sequence of the NP genes of all the GBNV isolates had a single open reading frame of 831 nucleotides and 276 amino acids. The isolates had among them 2% variability at amino acid level and 2‒3 variability at nucleotide level, but had variability with other GBNV isolates of fabaceous hosts in the range of 0‒6% at amino acid level and 1‒8% at nucleotide level. Though this variation in nucleotide sequences of GBNV isolates from fabaceous hosts is within the limits of species demarcation for tospoviruses, formation of a separate cluster within the GBNV isolates indicates the possibility of distinct variants in GBNV.